Zawiyah Shaykhkuala: Pusat penyebaran Islam di alam Melayu abad ke-17 masihi - Mohd Syukri Yeoh Abdullah (Universiti Kebangsaan Malaysia, 2009)
This writing traces the role of Shaykhkuala zawiyah as the centre for the propagation of Islam in the 17th century. This article also discusses other activities that were carried out by this zawiyah during that period, such as education, research, and astronomy. These activities have contributed greatly to the process of Islamization not only to the kingdom of Acheh but also to the whole of Malay Archipelago. The article concludes that all the dakwah activities that were carried out by Shaykhkuala zawiyah can be made as guidelines for today’s institutions in planning their own activities